Hydrogen Adsorption, Absorption, and Desorption at Palladium Nanofilms formed on Au(111) by Electrochemical Atomic Layer Deposition (E-ALD): Studies using Voltammetry and In Situ Scanning Tunneling Microscopy - Sheridan, Leah B; Kim, Youn-Geun; Perdue, Brian R; Jagannathan, Kaushik; Stickney, John L; Robinson, David B (Journal of physical chemistry. C, 2013)
Pd nanofilms were grown on Au(111) using the electrochemical form of atomic layer deposition (E-ALD). Deposits were formed by repeated cycles of surface-limited redox replacement (SLRR). Each cycle produced an atomic layer of Pd, allowing the reproducible formation of Pd nanofilms, with thicknesses proportional to the number of cycles performed. Pd deposits were formed with up to 30 cycles, in the present study, and used as a platform for studies of hydrogen sorption/desorption as a function of thickness. The SLRR cycle involved the initial formation of an atomic layer of Cu by underpotential deposition, followed by its galvanic exchange with PdCl4 2– ions at open circuit. The first three cycles were studied using in situ electrochemical scanning tunneling microscopy (EC-STM), which showed a consistent morphology from cycle to cycle and the monatomic steps indicative of layer-by-layer growth. Cyclic voltammetry was used to study the hydrogen sorption/desorption properties as a function of thickness in 0.1 M H2SO4. The results indicated that the underlying Au structure greatly influenced hydrogen adsorption, as did film thickness for deposits formed with fewer than five cycles. No hydrogen absorption occurred for the thinnest films, although it increased linearly for thicker films, producing an average H/Pd molar ratio of 0.6. Electrochemical annealing was shown to improve surface order, producing CVs that strongly resembled those characteristic of bulk Pd(111).